Critical Realism on Disruption as An Economic Recovery Policy in Indonesia - Endarti, Esa Wahyu; Wasiaturrahma, .; Sunyoto, Kodrat; Putra, Allen Pranata (Journal of Ecohumanism, 2024)
This study observes that after the second wave of Covid-19 is an economic revival, countries that recover faster from the economic crisis are those that are ready to win market competition. The urgency of this research is that the acceleration of economic recovery in Indonesia is very important to be observed and analyzed. The formulation of this research problem has two things, namely: 1) What is the potential for economic recovery based on the perspective of critical realism in disruption in Indonesia? 2) How to optimize the economic recovery policy strategy in Indonesia? The stages of research methods to achieve research objectives are qualitative through the use of in-depth interviews, focus group discussions and observations. Research informants are stakeholders who have public positions so that their credibility and arguments can be categorized as very good. The results of the study show that the priority program of import substitution policies has been implemented to reach 35% in 2022 and is predicted to continue to be improved as an effort to improve the national trade balance. The priority program of the import substitution policy has been implemented to reach 35% in 2022 and is predicted to continue to be improved as an effort to improve the national trade balance.